2018
DOI: 10.1371/journal.pone.0195691
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of three methods of disseminating information to improve medical male circumcision in Uganda

Abstract: BackgroundUganda is working to increase voluntary medical male circumcision (VMMC) to prevent HIV infection. To support VMMC quality improvement, this study compared three methods of disseminating information to facilities on how to improve VMMC quality: M—providing a written manual; MH—providing the manual plus a handover meeting in which clinicians shared advice on implementing key changes and participated in group discussion; and MHC—manual, handover meeting, and three site visits to the facility in which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
“…Descriptions of included cost studies and their outcomes are presented in Table 5. Seven of the included studies assessed community-based interventions [14,36,[40][41][42][43][44], two assessed school-based interventions [25,39], and two assessed facility-based interventions [37,38]. Generally, cost studies showed that service delivery interventions may create economies of scale and efficiencies when implemented widely.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To improve performance, coaches use multiple approaches, including modeling desired behaviors, providing supportive supervision, providing auditing and feedback, and promoting problem solving. 15 These strategies are effective at improving quality of care in low-and middle-income countries across a variety of clinical areas, 16,17 including Integrated Management of Childhood Illness, 18,19 drug management and prescription practices, 20,21 primary care, 22 malaria case management, 23 voluntary male circumcision, 24 and reproductive health. 25,26 Although some studies have reported associations between increased intensity of coachingrelated activities and improved quality of care, [21][22][23] the optimal coaching intensity needed to promote and sustain behavior change is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Expressed in terms of year 2020 US dollars, the estimates of the total costs of the D&I strategies ranged from $7288 27 to $3.0 million 28 for multicomponent strategies, excluding studies with incomplete cost information for all identified strategies [29][30][31] and studies that were designed to compare the effect of different strategies. [32][33][34][35][36][37][38] In contrast, the range was $212 39 -$4.4 million 40 for discrete D&I strategies (online supplemental table S4). No association was observed between the number of strategies used and the total cost, given the broad range of the D&I strategies and associated costs.…”
Section: Cost Estimates Of Dandi Strategiesmentioning
confidence: 99%